Case Report: A novel intergenic MIR4299/MIR8070-RET fusion with RET amplification and clinical response to pralsetinib in a lung adenocarcinoma patient - Wang, Sha-Sha; Wang, Fang; Zeng, Zhen; Gao, Fang; Liu, Huan-Huan; Wang, Hui-Na; Hu, Yi; Qin, Hai-Feng (Frontiers in Oncology, 2022)
The identification of receptor-tyrosine kinase gene (RET) fusions in lung cancer has become crucial owing to actionable events that predict responsiveness to tyrosine kinase inhibitors (TKIs). However, RET fusions with distinct partner genes respond differently to TKIs. In this case, a 60-year-old man was diagnosed with advanced lung adenocarcinoma. A novel RET-MIR4299/MIR8070 fusion and RET amplification were identified using next-generation sequencing (NGS). The patient was then administered with pralsetinib. After 3 weeks of therapy, the patient had a partial response. At the time of reporting, the patient was on continuous pralsetinib. These findings broaden the range of RET fusion types and provide the basis for the hypothesis that RET intergenic fusion and amplification respond to pralsetinib treatment in lung adenocarcinoma.